Environment and tourism - Holden, Andrew (London ; Routledge, 2008)
Examining the relationship that tourism has with the natural and cultural environment, this title analyses the meaning of environment and its various cultural perceptions and interpretations, focusing on how tourism brings change and impacts on environments
Keywords: Tourism -- Environmental aspects; Tourism; Tourism -- Social aspects